2015
DOI: 10.4081/ijas.2015.3535
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids Combined with Equine Chorionic Gonadotropin to Enhance Reproductive Performance in Aged Rabbit Does

Abstract: Sixty low-conception rate does aged 18 to 24 months (in four groups) were used to determine the effect of replacement of prostaglandin (PG) F2α (PGF2α) injection by oral administration with sunflower oil (Sun)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The obtained results in the present study clearly indicates that the use of 3.0% linseed oil improved the productive traits of does compared to the other two supplementation rates (1.5 and 4.5%) and the control ones. These results are in harmony with those recorded by Elkomy and El-Speiy (2015) who found that replacement of the prostaglandin-F2-alpha (PGF2α) injection by oral administration at the rate of 3 ml/doe/day of Linseed oil to old does improved litter size at birth by 21.9% and bunny body weight at birth by 22% compared to the control group. Similar results of daily weight gain for the insignificant effect of linseed oil supplementation obtained herein are reported by Zeweil et al (2016).…”
Section: Productive Traitssupporting
confidence: 88%
See 1 more Smart Citation
“…The obtained results in the present study clearly indicates that the use of 3.0% linseed oil improved the productive traits of does compared to the other two supplementation rates (1.5 and 4.5%) and the control ones. These results are in harmony with those recorded by Elkomy and El-Speiy (2015) who found that replacement of the prostaglandin-F2-alpha (PGF2α) injection by oral administration at the rate of 3 ml/doe/day of Linseed oil to old does improved litter size at birth by 21.9% and bunny body weight at birth by 22% compared to the control group. Similar results of daily weight gain for the insignificant effect of linseed oil supplementation obtained herein are reported by Zeweil et al (2016).…”
Section: Productive Traitssupporting
confidence: 88%
“…In this concern, Mattos et al (2000) explained that positive reproduction using diets supplemented with fats can take place by altering both ovarian follicles and corpus luteum function through increasing precursors for the synthesis of reproductive hormones such as steroids and prostaglandin. Elkomy and El-Speiy (2015) concluded that replacement of the prostaglandin-F2-alpha (PGF2α) injection by oral administration at the rate of 3 ml/doe/day of Sunflower or Linseed oils to old does improved sexual hormone synthesis and secretion, litter size at birth by 21.9% and bunny body weight at birth by 22% compared to the control group.…”
mentioning
confidence: 99%
“…Overall kindling rate at K1 was 76.5 and 86.5% for C and D rabbit does, respectively, which was higher than the fertility rate of another study on multiparous rabbit does (Elkomy and El-Speiy, 2015). Kindling rate of D multiparous does in K1 was higher than that reported in another study considering Pannon White rabbits (Szendr et al, 1999).…”
Section: Resultsmentioning
confidence: 54%
“…The overall mean of litter size at birth LSB, at 21 days and at weaning (28 days) were lower than litter sizes of New Zealand white and Hyplus breed at natural mating which presented by Heba- T-Allah et al (2016), also lower than litter size at birth (Total and Live) of Hyplus breed in Artificial Insemination which reported by Lebas et al (1996), and lower than litter size at birth which reported by Elkomy and El-Speiy (2015) and Oliveira et al, (2011), and in line with results presented by Oguike and Okocha (2008) in Dutch and Chinchilla crosses rabbit breeds of litter size at birth and at weaning. However, higher than results presented by El-Ratel et al (2017) and Kalaba and Abdel-Khalek (2011) in New Zealand White rabbit does and California rabbit does of litter size at birth (Total and Live), respectively, and at weaning in New Zealand White rabbit does (El-Ratel et al, 2017).…”
Section: Resultsmentioning
confidence: 72%